Effect of chemotherapy on cognition and depression among solid tumor cancer patients in a tertiary care hospital - Jenanee Velayutham; Jayasutha Jayram; A. Vengadeswaran; S. Sivasupriya; K. Malini Prithiva Kumari; N. Arunagiri; Charupriya; Lisiya; Lourdu Akshaya; Sindhu Selvam; Ravichandran A. Selvam (International Journal of Basic & Clinical Pharmacology, 2026)
Background: Chemotherapy is a key treatment modality for solid tumors but is often associated with cognitive impairment, depression, and reduced quality of life. Early identification of these complications is important for improving patient outcomes and treatment adherence. Methods: A prospective cohort study was conducted over six months in the Department of Medical Oncology, Sri Ramachandra Hospital, Chennai. Adult patients (18-65 years) with solid tumors receiving platinum-based agents, taxanes, or antitumor antibiotics were enrolled. A total of 267 patients completed the study. Cognitive function, depression, quality of life, and medication adherence were assessed at baseline and follow-up using the Functional Assessment of Cancer Therapy-Cognitive Function (FACT-Cog), Brief Edinburgh Depression Scale (BEDS), European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30), and Medication Adherence Rating Scale (MARS), respectively. Results: Among the 267 participants, females constituted the majority. Significant deterioration in cognitive function and increased depression scores were observed during chemotherapy, particularly among patients receiving platinum-based regimens. Depression scores showed significant worsening at weeks 8 and 12 in the platinum-based group (p